Episodic stimulation of central chemoreceptor neurons elicits disordered breathing and autonomic dysfunction in volume overload heart failure - Diaz, Hugo S.; Andrade, David C.; Toledo, Camilo; Pereyra, Katherin; Schwarz, Karla G.; Diaz-Jara, Esteban; Lucero, Claudia; Arce-Alvarez, Alexis; Schultz, Harold D.; Silva, Josiane N.; Takakura, Ana C.; Moreira, Thiago S.; et al. (My University, 2020)
Enhanced central chemoreflex (CC) gain is observed in volume overload heart failure (HF) and is correlated with autonomic dysfunction and breathing disorders. The aim of this study was to determine the role of the CC in the development of respiratory and autonomic dysfunction in HF. Volume overload was surgically created to induce HF in male Sprague-Dawley rats. Radiotelemetry transmitters were implanted for continuous monitoring of blood pressure and heart rate. After recovering from surgery, conscious unrestrained rats were exposed to episodic hypercapnic stimulation [EHS; 10 cycles/5 min, inspiratory fraction of carbon dioxide (FICO2) 7%] in a whole body plethysmograph for recording of cardiorespiratory function. To determine the contribution of CC to cardiorespiratory variables, selective ablation of chemoreceptor neurons within the retrotrapezoid nucleus (RTN) was performed via injection of saporin toxin conjugated to substance P (SSP-SAP). Vehicle-treated rats (HF+Veh and Sham+Veh) were used as controls for SSP-SAP experiments. Sixty minutes post-EHS, minute ventilation was depressed in sham animals relative to HF animals (Delta V-E: -5.55 +/- 2.10 vs. 1.24 +/- 1.35 mL/min 100 g, P < 0.05; Sham+Veh vs. HF+Veh). Furthermore, EHS resulted in autonomic imbalance, cardiorespiratory entrainment, and ventilatory disturbances in HF+Veh but not Sham+Veh rats, and these effects were significantly attenuated by SSP-SAP treatment. Also, the apneahypopnea index (AHI) was significantly lower in HF+SSP-SAP rats compared with HF+Veh rats (AHI: 5.5 +/- 0.8 vs. 14.4 +/- 1.3 events/h, HF+SSP-SAP vs. HF+Veh. respectively. P < 0.05). Finally. EHS-induced respiratory-cardiovascular coupling in HF rats depends on RTN chemoreceptor neurons because it was reduced by SSP-SAP treatment. Overall. EHS triggers ventilatory plasticity and elicits cardiorespiratory abnormalities in HF that are largely dependent on RTN chemoreceptor neurons.
Keywords: breathing disorders; chemoreflex; heart failure; retrotrapezoid nucleus; ventilatory plasticity